VALIDITAS DAN KEPRAKTISAN PROBLEM BASED LEARNING BERORIENTASI PENDEKATAN METAKOGNITIF - Arie Arma Arsyad; Ummu Kalsum; Masriani Masriani (Universitas Sulawesi Barat, 2022)
This study was a pre-experimental research that measures 1) the validity of the physics learning outcome instrument and 2) the practicality of the problem-based learning model oriented to a metacognitive approach to improve student learning mastery of SMA Negeri 1 Campalagian. Sampling using a purposive sampling technique with a total of 27 students for the 2018/2019 academic year. The design of this research was one group pretest posttest. The instrument used was the instrument of physics learning outcomes. The results showed that: 1) the validity of the learning outcomes instrument was 0.80 (high category) and 2) the implementation of the problem based learning learning process oriented to the metacognitive approach was at a score of 86.25 (good category). Thus, it can be concluded that problem based learning oriented to metacognitive approach was valid and practical.